Metabolic syndrome, hypertension, and nervous system injury: Epidemiological correlates. (2nd January 2017) - Ricci, Giovanna; Pirillo, Isabel; Tomassoni, Daniele; Sirignano, Ascanio; Grappasonni, Iolanda
ABSTRACT: Metabolic syndrome (MetS) is a common and complex disorder combining hypertension, obesity, dyslipidemia, and insulin resistance. MetS represents a risk factor for changes in cognitive functions in older age, and several studies have suggested that MetS may be linked to dementia. This article reviews the main evidences about the relationship between MetS and neurodegenerative disease. Starting from an epidemiological point of view, the article analyzes medico-social aspects related to MetS, considering the reduction of work capacity and the condition of disability that it involves. Some authors affirm that on the basis of current Italian legislation, it is possible to consider the syndrome as a disability. This is because all the diseases that make up MetS are high-risk clinical pathological conditions. For these reasons, a joint action is required to contain the incidence of MetS, the high social costs, and the loss of productivity related to the syndrome. In conclusion, healthcare initiatives could be adopted in order to increase the understanding of the pathogenic contributions of each element on MetS and how they can be modified. These actions will be useful to reduce healthcare costs and can lead to more effective prevention of metabolic disease, thus promoting good health. Abbreviations : MetS: Metabolic syndrome; WHO: World Health Organization; CVD: cerebrovascular diseases; AD: Alzheimer's Disease; VaD: Vascular Dementia; IDF: International Diabetes Federation; T2DM: type 2 diabetes mellitus; CAD: coronary artery disease; MCI: mild cognitive impairment; NCDs: Non Communicable Diseases; BMI: Body Mass Index; ICIDH: International classification of impairments, disabilities and handicaps